Holistic Personality and MBKM Decision-Making: Student Well-Being and Equitable Access in Indonesian Higher Education - Endah Kurniawati Purwaningtyas; Andik Rony Irawan; Triyo Supriyatno; Abd. Rahman Ambo’ Dalle (Women, Education, and Social Welfare, 2026)
Independent Learning–Independent Campus (Merdeka Belajar–Kampus Merdeka; MBKM) promotes off-campus experiential learning, yet the psychological conditions shaping participation and the equity implications of access remain underexamined. This multisite cross-sectional study tested the association between holistic personality and decision-making among 260 undergraduate MBKM participants at a State Islamic University and a Muhammadiyah university in Indonesia. Proportional random sampling was applied within the available participant frame. A structured questionnaire assessed holistic personality (experiential, attitudinal, and creative values) and MBKM decision-making (self-control, external control, and absence of control). Descriptive statistics, Cronbach’s alpha, and Pearson correlation were used. Most respondents reported moderate decision-making (80.8%; M = 30.50, SD = 6.21) and moderate holistic personality (65.4%; M = 138.54, SD = 14.88). Reliability was acceptable for decision-making (α = .67) and good for holistic personality (α = .81). Holistic personality correlated positively and moderately with MBKM decision-making (r = .477, p < .001). Self-control and experiential value were the dominant dimensions. The study contributes a psychological-equity account of MBKM: students’ capacity to regulate goals and derive meaning from experience is associated with more deliberate participation, but equitable participation requires information, financial, mobility, safety, and mentoring support. Universities should embed gender-responsive and welfare-sensitive safeguards in MBKM governance.